Heating profile of electro-conductive weft-knitted composite fabrics during cyclic deformation - Repon, Md. Reazuddin; Mikučionienė, Daiva (Wydawnictwo Politechniki Łódzkiej, 2022)
The goal of this research was to learn more about how heat is generated during cyclic deformation of highly conductive knitted composite fabric. The heating materials in this investigation were silver (Ag) coated polyamide (PA) yarn knitted into a pattern. At various time intervals, the temperature generated on the fabric surface was measured. An Instron tensile testing machine was used to perform the cyclic stress strain in the course direction of the developed fabric. The temperature on the conductive fabric surface increased rapidly for the first two minutes, then slowly afterward, eventually levelled off at a specific point. Heat generation is negatively influenced by stretching and cyclic deformation. Heat generation was also affected by the amount of conductive yarn used in the knitting design. The materials developed in this work could be employed in orthopaedic compression support to offer sufficient heating.
Keywords: electro-conductivity; heat generation; knitted fabrics; orthopaedic compression support; przewodnictwo elektryczne; wytwarzanie ciepła; dzianiny; ortopedyczne wspomaganie kompresji